Implementasi Nilai Kejujuran dalam Aktivitas Jual Beli Ternak dan Implikasi terhadap Pendidikan Karakter - Naufal Raid (JURNAL PENDIDIKAN ROKANIA, 2019)
Honesty is the main value that must exist in conducting buying and selling transactions on the market. Thisarticle aims to describe the form of implementation of honesty values that exist in livestock buying and selling transactions. The method used is a qualitative method with descriptive type. The results of the study show that there are still toke who do not implement honesty values in livestock buying and selling transactions. The solution offered is the need for strict sanctions from market officers for toke that are not honest.